Multiagent therapy with pomalidomide, bortezomib, doxorubicin, dexamethasone, and daratumumab (“Pom-PAD-Dara”) in relapsed/refractory multiple myeloma - Zhou, Xiang; Steinhardt, Maximilian J.; Grathwohl, Denise; Meckel, Katharina; Nickel, Katharina; Leicht, Hans-Benno; Krummenast, Franziska; Einsele, Hermann; Rasche, Leo; Kortuem, Klaus M. (Cancer Medicine, 2020)
Background: Even in the era of novel immunotherapies for multiple myeloma (MM), treatment of late-stage relapsed/refractory (RR) patients remains challenging. The aim of our study was to analyze the efficacy and safety of the five-drug combination pomalidomide, bortezomib, doxorubicin, dexamethasone, and daratumumab (“Pom-PAD-Dara”) in RRMM. Methods: We retrospectively analyzed data of 56 patients with RRMM who received Pom-PAD-Dara between September 2016 and May 2019. Results: Patients were heavily pretreated with a median of four prior lines of therapy, including autologous and allogenic stem cell transplant in 50 (89%) and six (11%) patients, respectively. The overall response rate (ORR) was 78% and we observed partial remission, very good partial remission, and complete remission in 27 (48%), 13 (23%) and four (7%) patients, respectively. Median progression-free survival was 7 months (95% CI, 3.3-10.7) and the median overall survival was not reached at 24 months. Adverse events grade ≥ 3 were observed 41 (73%) patients and included neutropenia (n = 28, 50%), anemia (n = 22, 39%), thrombocytopenia (n = 21, 38%), and pneumonia (n = 6, 11%). Conclusion: Pom-PAD-Dara represents a promising multiagent regimen in heavily pretreated RRMM patients with high ORR and an acceptable safety profile.
CRIS-Team Scopus Importer:2023-03-23
Keywords: multiple myeloma; Pom-PAD-Dara; refractory; relapse